Phytochrome A null mutants of Arabidopsis display a wild-type phenotype in white light. - Whitelam, G; Johnson, E; Peng, J; Carol, P; Anderson, M; Cowl, J; Harberd, N (1993)
Phytochrome is a family of photoreceptors that regulates plant photomorphogenesis; the best-characterized member of this family is phytochrome A. Here, we report the identification of novel mutations at three Arabidopsis loci (fhy1, fhy2, and fhy3) that confer an elongated hypocotyl in far-red but not in white light. fhy2 mutants are phytochrome A deficient, have reduced or undetectable levels of PHYA transcripts, and contain structural alterations within the PHYA gene. When grown in white light, fhy2 mutants are morphologically indistinguishable from wild-type plants. Thus, phytochrome A appears to be dispensable in white light-grown Arabidopsis plants. fhy2 alleles confer partially dominant phenotypes in far-red light, suggesting that the relative abundance of phytochrome A can affect the extent of the far-red-mediated hypocotyl growth inhibition response. Plants homozygous for the recessive fhy1 and fhy3 mutations have normal levels of functional phytochrome A. The FHY1 and FHY3 gene products may be responsible for the transduction of the far-red light signal from phytochrome A to downstream processes involved in hypocotyl growth regulation.